A new injury prevention programme for children's football – FIFA 11+ Kids – can improve motor performance: a cluster-randomised controlled trial. Issue 6 (18th March 2016) - Rössler, R; Donath, L; Bizzini, M; Faude, O
ABSTRACT: The present study evaluated the effects of a newly developed injury prevention programme for children's football ("FIFA 11+ Kids") on motor performance in 7–12-year-old children. We stratified 12 football teams (under-9/-11/-13 age categories) into intervention (INT, N = 56 players) and control groups (CON, N = 67). INT conducted the 15-min warm-up programme "FIFA 11+ Kids" twice a week for 10 weeks. CON followed a standard warm-up (sham treatment). Pre- and post-tests were conducted using: single leg stance; Y-balance test; drop and countermovement jump; standing long jump; 20-m sprint; agility run; slalom dribble; and wall volley test. We used magnitude-based inferences and linear mixed-effects models to analyse performance test results. We observed likely beneficial effects favouring INT in Y-balance (right leg; +3.2%; standardised mean difference (SMD) = 0.34; P = 0.58) and agility run (+3.6%; SMD = 0.45; P = 0.008). Possibly beneficial effects were found in Y-balance, drop jump reactive strength index, drop jump height, countermovement jump, standing long jump, slalom dribble and wall volley test. At least possibly beneficial improvements in favour of "FIFA 11+ Kids" were observed in nearly all parameters. Most effects were small, but slight improvements in motor performance may potentially contribute to a reduction of injury risk.